2016
DOI: 10.21275/v5i7.art2016604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Fruit Oil (Pandanus Conoideus Lam) on Animal Model of Preeclampsia

Abstract: Preeclampsia is a complication of pregnancy with hypertension and proteinuria as major symptomps. Although the pathogenesis of preeclampsia is not yet clear, the role of oxidative stress had been proven by several studies. The role of antioxidants in preventing preeclampsia also had been reported. Red fruit oil (RFO), extracted from red fruit (Pandanus conoideus Lam), is rich in antioxidants vitamin E and β-carotene. The aims of this study were to investigate the potency of RFO in the prevention of preeclampsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…PC Lam had been proven as a non-toxic drug [18], thus it is relatively safe to consume for a long time. In this study, the rats have received a dose of 0.2-0.4 cc which had been proven to resolve oxidative stress in the preeclampsia animal model according to Sugiritama et al (2016) [16]. In addition, many animal studies had confirmed the antioxidant activity of IB due to its secondary metabolite anthocyanin, as well as its safety at appropriate doses [7], [8], [9], [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC Lam had been proven as a non-toxic drug [18], thus it is relatively safe to consume for a long time. In this study, the rats have received a dose of 0.2-0.4 cc which had been proven to resolve oxidative stress in the preeclampsia animal model according to Sugiritama et al (2016) [16]. In addition, many animal studies had confirmed the antioxidant activity of IB due to its secondary metabolite anthocyanin, as well as its safety at appropriate doses [7], [8], [9], [19].…”
Section: Discussionmentioning
confidence: 99%
“…The Ethics Committee of Faculty of Medicine, Udayana University, Bali, Indonesia had been approved this study (No: 3070/UN14.2.2.VII.14/LP/2019). The method for preparation IB L tablet was the same as the previous study by Yasa et al [12] and PC Lam oil was extracted according to the previous study by Sugiritama et al [16].…”
Section: Animal Modelsmentioning
confidence: 99%